Efektivitas Ekstrak Daun Jambu Biji (Psidisium Guajava L) Terhadap Penurunan Frekuensi Diare pada Anak Usia 6-12 Tahun di Puskesmas Aceh Besar - Cut Rara Hasviana; Nanda Desreza; Riyan Mulfianda (Viva Medika, 2022)
In developing countries, diarrhea is a common disease and a leading cause of mortality in children. Moreover, the guava plant (Psidium guajava L) is known by the Indonesian people as herbal medicine that may serve as a remedy for various diseases. One of the best-known benefits of guava leaf for people in Indonesia is that it can act as an antidiarrheal. This study aimed to examine the effectiveness of guava leaf extract (Psidium Guajava L.) in diarrhea treatment among children aged 6-12 years in the working area of Krueng Barona Jaya Community Health Center. This study was a quasi-experiment of One-Group Pretest-Posttest Design. The population member in this study was mothers with children aged 6-12 years old suffering from diarrhea in the working area of Krueng Barona Jaya Public Health Center. The purposive sampling technique was employed to select 15 respondents. Data collection was done by distributing questionnaires to respondents. This study was conducted from 27 June to 4 July 2022. The data were processed using editing, coding, transferring, and tabulating, and analyzed using the T-test at an error level of 0,05. The results showed that is effective in diarrhea treatment for children aged 6-12 years old with a p-value of 0.000